Topics in Modal Analysis, Volume 7 Proceedings of the 31st IMAC, A Conference on Structural Dynamics, 2013 - Allemang, Randall.; Allemang, Randall.; De Clerck, James.; De Clerck, James.; Niezrecki, Christopher.; Niezrecki, Christopher.; Wicks, Alfred.; Wicks, Alfred. (Conference Proceedings of the Society for Experimental Mechanics Series,, 2014)
Topics in Modal Analysis, Volume 7:  Proceedings of the 31st IMAC, A Conference and Exposition on Structural Dynamics, 2013, the seventh volume of seven from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on:   Fluid Structure Interaction Adaptive Structures Experimental Techniques Analytical Methods Damage Detection Damping of Materials & Members Modal Parameter Identification Modal Testing Methods System Identification Active Control Modal Parameter Estimation Processing Modal Data.